Does the '2012 IUSTI ECCG report on the diagnosis and management of Neisseria gonorrhoeae infections in Europe' depict the situation in Europe?. (June 2013) - Unemo, M; Brooks, B; Cole, M; Ross, J D C; White, J A; Patel, R
Summary: Gonorrhoea is a major public health concern globally. Of particular grave concern is that resistance to the third generation cephalosporins has been identified during recent years. This paper summarises and discusses the results of the '2012 IUSTI European Collaborative Clinical Group (ECCG) report on the diagnosis and management of Neisseria gonorrhoeae infections in Europe'. Although high quality care was reported in many settings, in several other countries the testing, diagnostics, antimicrobial treatment and follow-up of gonorrhoea patients need to be optimized. This, together with increased access to and use of antimicrobial susceptibility testing, is crucial in controlling the emergent spread of cephalosporin-resistant and multidrug-resistant gonorrhoea.